2006
DOI: 10.1152/ajpgi.00321.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of caveolin-1 knockout on NANC relaxation in circular muscles of the mouse small intestine compared with longitudinal muscles

Abstract: . Impact of caveolin-1 knockout on NANC relaxation in circular muscles of the mouse small intestine compared with longitudinal muscles. Am J Physiol Gastrointest Liver Physiol 290: G394 -G403, 2006. First published September 15, 2005 doi:10.1152/ajpgi.00321.2005.-Recently, we showed that caveolin-1 (cav1) knockout mice (Cav1 Ϫ/Ϫ mice) have impaired nitric oxide (NO) function in the longitudinal muscle (LM) layer of the small intestine. The defect was a reduced responsiveness of the muscles to NO compensated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…In addition, cAMP was postulated to produce relaxation in the intestinal smooth muscles by PKA-independent mechanisms such as the activation of uncoupling protein 1 (45) or cross activation of PKG (28). In previous studies, we showed that smooth muscle relaxation downstream of nitric oxide is reduced in cav1 Ϫ/Ϫ as a result of a defective soluble guanylate cyclase function (11,12), but the function of PKG was not tested.…”
Section: Cav1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cAMP was postulated to produce relaxation in the intestinal smooth muscles by PKA-independent mechanisms such as the activation of uncoupling protein 1 (45) or cross activation of PKG (28). In previous studies, we showed that smooth muscle relaxation downstream of nitric oxide is reduced in cav1 Ϫ/Ϫ as a result of a defective soluble guanylate cyclase function (11,12), but the function of PKG was not tested.…”
Section: Cav1mentioning
confidence: 99%
“…We also found that caveolin-1 knockout (cav1 Ϫ/Ϫ ) mice, which lack caveolin-1 and most caveolae, have an altered response to nitric oxide and other nonadrenergic, noncholinergic mediators in the small intestine (11,12). In the present study, we investigated alterations of GIT motility in the cav1 Ϫ/Ϫ mice small intestine associated with ␤-adrenoceptor function.…”
mentioning
confidence: 89%
“…Mice deficient in Cav-1 display increased nitric oxide (NO) production from increased eNOS activity (Razani et al, 2001) with resultant increased vascular permeability in mouse lung endothelium (El-Yazbi et al, 2006), both of which are reversed by injection of a truncated Cav-1 peptide containing the CSD. Inhibition of eNOS by caveolin occurs within the systemic vascular endothelium, whereby eNOS activity does not respond to regulatory signals, NO levels remain increased, and basal cGMP levels remain elevated in rings of aorta from Cav-1 deficient mice (Drab et al, 2001; Razani et al, 2001).…”
Section: Caveolins Coordinate Multiple Signaling Pathways In the Heartmentioning
confidence: 99%
“…In caveolin1 knockout animals, there is both a loss of the myogenic nNOS isoform and also a reduced NO mediated relaxation to nerve stimulation, compensated in part by an increased response of apamin sensitive inhibitory mediators [52,53]. The site of failure appears to be downstream from mediator release and associated with decreased responses to NO donors, sodium nitroprusside and S-nitroso-Nacetyl penicillamine.…”
Section: Functional Experimentsmentioning
confidence: 99%